2022
DOI: 10.47371/mycosci.2022.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Soil propagule banks of ectomycorrhizal fungi associated with <i>Larix cajanderi</i> above the treeline in the Siberian Arctic

Abstract: At invasion fronts, seedling mortality may increase if they fail to form associations with symbiotic fungi in the early developmental stages (Collier & Bidartondo, 2009). Trees that form northern treelines are obligately associated with ectomycorrhizal (EM) fungi that improve water and nutrient absorption by the host plants. EM associations may provide plants with direct access to mineralized nutrients that are released from organic matter by fungal enzyme activity (Lindahl & Tunlid, 2015;Shah et al., 2016). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
(120 reference statements)
1
2
1
Order By: Relevance
“…Nevertheless, it seems reasonable to compare our results with data on fungal diversity obtained using DNA barcoding. It was unexpected that the taxonomic diversity of mycorrhiza-forming basidiomycetes established in a study of Arctic communities involving larch [46] was found to be lower than that obtained in our studies. This work revealed the presence of only nine operational taxonomic units (OTUs) in the communities under study, in contrast to the 37 species we identified (Figure 5).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, it seems reasonable to compare our results with data on fungal diversity obtained using DNA barcoding. It was unexpected that the taxonomic diversity of mycorrhiza-forming basidiomycetes established in a study of Arctic communities involving larch [46] was found to be lower than that obtained in our studies. This work revealed the presence of only nine operational taxonomic units (OTUs) in the communities under study, in contrast to the 37 species we identified (Figure 5).…”
Section: Discussioncontrasting
confidence: 94%
“…This work revealed the presence of only nine operational taxonomic units (OTUs) in the communities under study, in contrast to the 37 species we identified (Figure 5). This discrepancy is likely due to the greater diversity of plant communities that were studied in this work compared to that of [46]. A total of 115 amplicon sequence variants (ASVs) belonging to the basidiomycetes were identified in the soils of Spitsbergen, representing 13.07% of the total fungal diversity [47].…”
Section: Discussionmentioning
confidence: 92%
“…In terms of climate preferences, C. geophilum not only favors moderately cold climates but also exhibits physiological adaptations to extreme cold. The survival of C. geophilum in the Arctic further supports this observation (Miyamoto et al, 2022 ). Additionally, C. geophilum can thrive even under relatively arid conditions, potentially due to its ability to regulate osmotic pressure, and enhance antioxidant enzyme activity and alleviate drought stress (Li, Yuan, et al, 2022 ).…”
Section: Discussionsupporting
confidence: 64%
“…bovinus, S. luteus, and R. sinensis [19][20][21] , respectively. The ITS sequence of S3 (OM865366) showed 99.03% homology with the Japanese S. grevillei [22] . The original fruiting bodies were sampled from coniferous and broad-leaved mixed forests in Yantai, China, at Xiaoyuanmiao Forest Farm and Trapped Mountain Forest Farm (Table 1).…”
Section: Resultsmentioning
confidence: 99%